Pengaruh Gaya Kepemimpinan dan Komunikasi terhadap Kinerja Pegawai di Kantor Camat Pandan Kabupaten Tapanuli Tengah - Renova Lasmaria Samosir (Neolectura, 2021)
This study aims to determine and analyze the influence of leadership and communication styles on employee performance in the District Office of Pandan District, Central Tapanuli Regency. This research is a quantitative research. Data collection techniques using a questionnaire. The data analysis technique used is statistical analysis based on SPSS multiple regression. The population in this study were all employees in the District Office of Pandan District, Central Tapanuli Regency with 80 employees. The research sample uses a saturated sample technique in which the entire population is sampled. The results of this study indicate that the leadership and communication styles partially and simultaneously have a significant effect on the performance of employees in the District Office of Pandan District, Central Tapanuli Regency.